Virtual learning during the COVID-19 pandemic: What are the barriers and how to overcome them? - Sujata Yadneshwar Khobragade; Htoo Htoo Kyaw Soe; Yadneshwar Sudam Khobragade; Adinegara Lutfi bin Abas (Wolters Kluwer Medknow Publications, 2021)
CONTEXT: Virtual learning is not without challenges. It can cause stress, lack of motivation, and social isolation. Due to COVID-19 pandemic, our college shifted from face-to-face to virtual teaching-learning style. the aim was to find out the barriers in virtual learning among medical students and provide solutions to overcome them. MATERIALS AND METHODS: This cross-sectional study was conducted among 3rd- and 4th-year Bachelor of Medicine and Bachelor of Surgery students in 2020. Prevalidated electronic survey forms on institutional barrier, technical barrier, and individual barrier were sent to students, 160 students responded. SPSS version 12 was used to calculate descriptive statistics and independent t-test. RESULTS: The students had the highest mean score in individual barrier (mean: 2.82 [standard deviation (SD): 0.72]) followed by institutional barrier (mean: 2.79 [SD: 0.74]) and technological barrier (mean: 2.72 [SD: 0.75]). Regarding technological barriers, 38.6% of the students agreed difficulty in procurement of the laptop and 66.4% faced slow Internet connection. Regarding institutional barriers, 75.9% were stressed to join one lecture to another lecture as the lectures were continuous, 69.6% had limited opportunity to interact with lecturers, and 62.7% had poor communication between lecturers and students. Regarding individual barriers, 74.1% of the students were not motivated for online learning, 71.5% of the students could not learn as well as they were in the classroom, and 58.2% disagreed taking online courses in future. CONCLUSION: Low motivation, communication, Internet connectivity, and technical problems were the main barriers. Smaller size class, highly motivated and well-trained lecturers, and interactive lectures may help in breaking the barriers of virtual learning.